Possible brain manifestations and sequelae in patients infected with SARS-CoV-2: a narrative literature review - Figueiredo, Bárbara Queiroz de (2021)
Introduction: SARS-CoV and SARS-CoV-2 belong to the genus betacoronavirus, of the family Coronaviridae, of the order Nidovirales. Such viruses are enveloped by a positive-sense single-stranded RNA genome and infect humans by affecting the lower respiratory tract. In the current pandemic scenario, it has been reported that, in addition to common flu manifestations, SARS-CoV-2 (the etiological agent of COVID-19) can cause complications in various organic systems, such as the cardiovascular and supposedly nervous. Objective: Prove or contradict the hypotheses related to neurological complications triggered by Sars-CoV-2. Search methodology: This is a descriptive literature review research in the following databases: PubMed, Scielo, CDSR, Google Scholar, BVS and EBSCO, with the descriptors "SARS-CoV-2", "neurological symptoms", "COVID-19", "spike protein", "neuroinvasion", "ACE2". Discussion: Coronaviruses can cause severe pulmonary manifestations that require intensive care unit treatment and, thus, infected patients may also suffer from indirect neurological complications of critical illnesses. Thus, the involvement of the central and peripheral nervous system may be related to hypoxia and endothelial damage, uncontrollable immune reaction and inflammation, in addition to other effects, mainly circulatory. Finally, the hypothesis about the neuroinvasive and neurovirulence properties of SARS-CoV-2 is based on the following evidence: biological plausibility of the involvement of the central nervous system (CNS) by other respiratory viruses and the illustration of cases of patients with COVID-19 that presented neurological manifestations. Final considerations: In this study, it was possible to see that patients affected by COVID-19 often have neurological involvement, especially elderly people with multiple risk factors.